META-ANALYSIS OF BEHAVIOURAL INTERVENTIONS OF ENURESIS IN SPAIN - Rosa Alcázar, Ana Isabel; Olivares Rodríguez, José; Sánchez Meca, Julio (Anales de Psicología / Annals of Psychology, 1999)
In this paper the results of a meta-analytic reviewabout the differential effectiveness of the three main behaviouralinterventions on subjects with problems of enuresisare presented: Mowrer’, Azrin’, and Kimmel’s techniques.A total of 14 independnet primary studies carriedout in Spain between 1980 and 1996 were integrated. Theeffect size index selected was the standardised mean difference,d, achieving an average value of d+ = 1.286. The resultsshowed significant differences among the three interventiontechniques, standing out the Azrin’ and Mowrer’sones. Other moderator variables are also analysed. Finally,the theoretical and clinical implications of the results arediscussed.